Exit dynamics of start-up firms. Does profit matter? - Rolf Golombek; Arvid Raknerud (Statistics Norway, Research Department, 2012)
While little attention has been paid to the role of profitability in the empirical literature on firm exit, we employ a detailed recently established database of Norwegian manufacturing firms to identify the extent to which profitability explains a firm's exit behavior. Some key characteristics of the data are: i) 25 percent of firms that exited experienced positive profits every year before exit, ii) there is no negative profitability shock immediately prior to exit, and iii) firms may continue production, even though they frequently experience negative profits. We use these data to estimate a theory-founded econometric model of exit, where the exit and investment decisions of firms are formulated as the solution to a discrete-continuous dynamic programming problem. In particular, the probability of exit depends on profitability, which is not directly observable to the econometrician. We estimate this model for six manufacturing industries and find that increased profitability lowers the probability of exit and that this effect is statistically significant in all industries. We show that the difference in annual exit probability between firms that exited during the observation period (1994-2009) and firms that did not exit is highly persistent over time, and there is no tendency for a sharp increase in the estimated exit probability just prior to exit. Hence, it is the cumulative effect of the higher risk of exit over several years, compared with the average firm, that causes firms to exit.
Keywords: C33; C51; C61; C72; D21; 330; Exit; investments; entrepreneurship; continuous-discrete choice; monopolistic competition; manufacturing firms; policy simulation; ownership structure; wage raise.